BIOGEOCHEMISTRY OF ELEMENTS IN LIGHT SIEROZEMS (Scientific journal of the Fergana State University, 2024)
The composition, amount and coefficient of biological absorption of Na, K, Mn, Sm, Re, Mo, Lu, U, Yb, Au, Nd, As, W, Br, Ca, La, Ce, Se, Hg, Tb, Th, Cr, Hf, Ba, Sr, Cs, Ni, Sc, Rb, Zn, Co, Ta, Fe, Eu, Sb in light sierozems and medicinal plants. It has been proved that, according to the coefficient of biogeochemical activity, the elements Se, Re, Br, K, Mo belong to the group of biological accumulation, and the rest of the studied macro- and microelements belong to the group of biological capture (KBP˂1).